Re-design Business Process at Forwading Company Based on EAP - Johanes Fernandes Andry; Pranchis Ranting (Universitas Multimedia Nusantara, 2019)
To be able to become a service company that is superior to other service companies, it requires assistance from the application of IS / IT in its business processes. Both main activities and supporting activities. Enterprise Architecture Planning or EAP helps make planning for the implementation of IS / IT more mature and better, so that the implementation of IS / IT in the company's business processes can run and work in accordance with the company's vision and mission. Zachman Framework is one method that can be used to help do EAP. The Zachman Framework will map the entire system in the company based on 6 different viewpoints along with 5W + 1H. Therefore, this research is expected to be able to provide input to companies that are the object of research to implement IS / IT in accordance with business processes and vision and mission. Later the results of this study will be in the form of proposals for new business processes both supporting activities and the main activities of companies that use the application of IS / IT in them.